An Early Presentation of a Genomic Variant of Mucopolysaccharidoses II in a Female Newborn Baby - Ritesh, -; Singh, Harsh Mohinder (Journal of Nepal Paediatric Society, 2018)
Mucopolysaccharidoses II is a X-linked genetic disorder caused by the deficiency of lysosomal enzyme Iduronate sulfate sulfatase due to mutations of Iduronate 2-sulfatase (IDS) gene which results in accumulation of intralysosomal glycosaminoglycan. X inactivation and gene alterations are known to cause this entity in a female child. We report an unusual case of missense mutation of IDS gene in heterozygous variant with dominant expression in a female neonate presented in early newborn period with incurable severity. X- linked recessive (heterozygous) missense mutation of Exon 8 in IDS gene confirmed a case of Mucopolysaccharidoses II by Sanger sequencing.